Antibody-mediated rejection. Issue 5 (October 2015) - Westall, Glen P.; Paraskeva, Miranda A.; Snell, Greg I.
<x xml:space="preserve">Abstract</x> Purpose of review Pulmonary antibody-mediated rejection (AMR) while contributing to acute and chronic allograft dysfunction remains a diagnostic and therapeutic challenge. The diagnostic tenets upon which AMR is defined will be reviewed in the light of recent studies. Recent findings The introduction of solid phase assays such as the Luminex platform has provided a wealth of quantitative data on the presence of anti-human leukocyte antigen (HLA) donor-specific antibodies (DSA). Further studies are required to better define the relationship of circulating DSA and activation of proinflammatory immune pathways that result in allograft dysfunction. The limitations of C4d staining in defining AMR are highlighted from recent studies in lung transplantation and from the 2013 Banff meeting on renal transplantation. Summary The current challenge to the lung transplant community is to agree on a working definition of pulmonary AMR. Only then can we better appreciate the epidemiology, clinical phenotypes, and treatment of AMR.